Analysisof The Implementationand Impactof The Co-operative Learning Model (STAD Type) on Student Achievement : Literature Review - Hakim, Ari Choiruman; Sunardi, Sunardi; Djono, Djono (Social, Humanities, and Educational Studies (SHES): Conference Series, 2023)
This study aims to describe the application of various STAD type coopera-tive learning models in an effort to improve student learning outcomes. This research was conducted using a systematic literature review method. Data sources that later became the sub ject of this study consisted of 10 selected articles based on a review of keywords and the year of publication of rele-vant scientific articles and books, the keywords used were 'STAD', 'learning outcome', 'students achievement'. The article database comes from Google Scholar, Scopus.com, and Doaj.com. The data analysis technique in this re-search uses descriptive analysis techniques. The results of this study indicate that the application of the STAD type cooperative learning model can be ap-plied to various levels of education, besides that its application can also be adapted to various subjects which have proven to be quite effective in con-tributing to improving student learning outcomes. It was identified through 10 studies reviewed that students tend to be more active and able to collabo-rate in completing their assignments when teachers apply this learning model. So that this learning model can certainly be adopted by other subject teach-ers.